A biointegrated system for improving production efficiency of water recirculating aquaculture - Saleem Mustafa; Mohamadu Boyle Jalloh; Neoh, Seong Lee (Universiti Malaysia Sabah, 2010)
This research was focused on addressing three questions: 1) reliability of conventional aquaponics water recirculation system; 2) feasibility of farming plant crops on a stacked planting unit (SPU), and 3) practicability of stacked aquaponics systems. Portulaca spp. was planted in three different solutions: distilled water, aquaculture effluent, and fertilized water (with commercial hydroponic fertilizer). After 40 days of growth, the plants in the fertilized water recorded 145% more biomass gain compared to plants in aquaculture effluent. Physiological development of plant was observed to be markedly superior in the fertilized water compared to the other treatments. Another experiment was conducted by investigating the efficiency of Ipomea aquatica in remediating aquaculture effluent. Plants with well developed roots had their roots submerged in aquaculture effluent for seven days and it was found that nitrate and phosphorus were reduced by 59% and 65%, respectively. The two experiments suggested that although phytoremediation is relatively reliable, a different approach in aquaponics recirculation strategy had to be adopted as the growth performance of plants is unsatisfactory. SPU is a structure with planting rows stacked atop each other in A-shaped structure. Sweet Basil (Omicum basilicum) and Pak Choy (Brassica rapa) were grown in the SPU and their biomass gain was recorded for each row. Basil represented a medium sized plant and Pak Choy represented a short plant. It was found that even for this two very different plants, they recorded an identical effiCiency of 67% ± 1%. SPU accommodated 108% more plant in an area of land when compared with the conventional planting unit. It was found that the increased plant number per area in the SPU compensated for the non-ideal effiCiency. Pak Choy yielded 2.77 kg/m2 and Basil 1.51 kg/m2 more than the conventional planting unit. It was also found that the RAS system used in this research would make a loss of RM4751 per year, but if it is joined to the SPUs, forming stacked aquaponics, the system as a whole, would return a profit.